Biases in a humorous talk show on religious conversion on youtube: Critical discourse analysis approach on “Pindah Arah” playlist - Mufti Labib Jalaluddin; Zezen Zaenal Mutaqin (Universitas Muhammadiyah Malang, 2023)
Violations of religious freedom, including the right of religious conversion, often occur in Indonesia, although the state constitution guarantees the right. Several kinds of research indicate that news media has produced discursive violations through texts with certain language styles. Nonetheless, the violation can also happen through humorous language style in social media. This paper aims to discover the discourse behind a humorous talk show on religious conversion in the “Pindah Arah” playlist on the Comedy Sunday YouTube channel, whether it entirely promotes religious conversion as freedom of religion or carries bias. The playlist, as well as the channel, is chosen as the only one that gives the stage for religious converts, either those who converted to Islam or from Islam, to tell their religious conversion in a humorous program on YouTube. This qualitative research uses content analysis, applying Norman Fairclough’s critical discourse analysis method. The results of this study show that the videos in the playlist, on the one hand, show religious freedom, but on the other hand, they still carry the hosts’ majority bias. The bias is shown through word and analogy choices which frame conversion to Islam as positive and conversion from Islam as unfavorable. The bias is related to the social context among the social relationship between adherents of religions. This article argues that the playlist “Pindah Arah” of the Comedy Sunday YouTube channel implicitly violates personal freedom of religious conversion through aggressive humor and shows a contradiction between their slogan and jokes. Pelanggaran terhadap kebebasan beragama, termasuk hak untuk berpindah agama, tidak jarang terjadi di Indonesia meskipun secara hukum hak tersebut dijamin oleh konstitusi. Banyak penelitian menunjukkan adanya pelanggaran tersebut, terlebih dari wacana yang dimuat dan diproduksi oleh media berita melalui teks dengan gaya bahasa tertentu. Meski demikian, pelanggaran itu dapat terjadi melalui gaya bahasa humor di media sosial. Artikel ini bertujuan untuk menemukan wacana di balik talkshow lucu tentang konversi agama dalam playlist